Do voters learn? Evidence that voters respond accurately to changes in political parties' policy positions. Issue 2 (4th March 2017) - Seeberg, Henrik Bech; Slothuus, Rune; Stubager, Rune
Abstract: A premise of the mass–elite linkage at the heart of representative democracy is that voters notice changes in political parties' policy positions and update their party perceptions accordingly. However, recent studies question the ability of voters accurately to perceive changes in parties' positions. The study advances this literature with a two-wave panel survey design that measured voters' perception of party positions before and after a major policy shift by parties in the government coalition in Denmark 2011–2013. Two key findings extend previous work. First, voters do indeed pay attention to parties when they visibly change policy position. Second, voters update their perceptions of the party positions much more accurately than would have been expected if they merely relied on a 'coalition heuristic' as a rule-of-thumb. These findings imply that under some conditions voters are better able to make meaningful political choices than previous work suggests.